Pemanfaatan potensi bambu sebagai pemberdayaan ekonomi masyarakat berbasis Asset Based Community Development di Desa Bringsang Giligenting - Nabila Yuli Firdaus; Nasidatul Usriyah; Najwa Muqoddas; Nurul Huda Farisya; Orisa Sativa Nathifah; Muhammad Reza Ali Syah; Mujiburrohman Mujiburrohman; Noer Moh Bahrul Fauzi; Ria Astuti (IAIN Madura, 2022)
Bamboo is a very useful plant for the community's economic life. Traditionally, generally, bamboo can be used for various purposes, such as household utensils, handicrafts, and foodstuffs. Currently, the potential in the form of bamboo is abundant but still needs to be utilized by the community in Bringsang Village. Giligenting District, Sumenep Regency. This service-based research aims to carry out training and mentoring programs for the community regarding the utilization of bamboo assets as souvenirs with high economic value. The approach in this study uses the Aset Based Community Development (ABCD) method, which focuses on local assets, potential and domestic strengths. This research starts with production training, product branding training, and online and offline Marketing Training. This service-based research succeeded in creating souvenirs from bamboo in the form of key chains, decorative lights, figures, food plates, and drinking bottles with the branding